Infiltrative Hepatocellular Carcinoma: Transcatheter Arterial Chemoembolization Versus Hepatic Arterial Infusion Chemotherapy - An, Chao; Zuo, Mengxuan; Li, Wang; Chen, Qifeng; Wu, Peihong (Frontiers in Oncology, 2021)
Aims: To compare the effectiveness, safety, and survival outcomes in patients with infiltrative hepatocellular carcinoma (HCC) who underwent hepatic arterial infusion chemotherapy (HAIC) and transarterial chemoembolization (TACE). Methods: A total of 160 patients with infiltrative HCCs who underwent initial TACE (n = 68) and HAIC (n = 92) treatment from January 2016 to March 2020. We applied the propensity score matching (PSM) to adjust for potential imbalances. The overall survival (OS), progression-free survival (PFS), objective response rate (ORR) and disease control rate (DCR) were compared between two groups. Multivariate analysis was evaluated through the forward stepwise Cox regression model and β coefficients was applied for the nomogram construction. Results: The median follow-up duration for the study population was 20.8 months. After PSM, the median OS and PFS in the HAIC group were significantly higher than those in the TACE group (OS, 13.3 vs 10.8 months; p = 0.043; PFS, 7.8 vs 4.0 months; p = 0.035) and the ORR and DCR in the HAIC group were significantly higher than those in the TACE group (ORR, 34.8% vs 11.8%; p = 0.001; DCR, 54.3% vs 36.8%; p = 0.028). A nomogram model comprising albumin-bilirubin grade, treatment responses, sessions, and treatment modalities, showed good predictive accuracy and discrimination (training set, concordance index [C-index] of 0.789; validation set, C-index of 0.757), which outperformed other staging systems and conventional indices. Conclusion: HAIC improve significantly survival compared to TACE in patients with infiltrative HCC. A prospective randomized trial is ongoing to confirm this finding.